Climate-Smart Village Report: Taung Khamauk Village, Myanmar - Thant, Phyu Sin; Myae, Chan; Barbon, Wilson John; Naung, Ye Win; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Taung Khamauk village is located in Naung Shwe Township, Southern Shan State. The village is situated 3700 feet above sea level. Hills dominate the village topography with moderate to deep-sloping lands. The primary livelihoods of the village are agriculture and others such as selling fire wood, casual labor, and construction labor. Water scarcity is a significant challenge for agricultural productivity. Rainwater is harvested and stored for domestic use for a year long. Taung Khamauk was designated as a climate-smart village where participatory action research was undertaken from 2019 to 2020 to find solutions to the challenges posed by climate change on the lives and livelihoods of local farmers. In this project, IIRR promoted the CSV approach, facilitating community-based adaptation (CBA) processes, and a portfolio of CSA options is derived. With support from the International Development Research Centre (IDRC) Canada, the research project was implemented in Myanmar from July 2020 to July 2022. The purpose of this brief is to describe the updated profile of Taung Khamauk village in Southern Shan State, Myanmar, from 2019 to 2022.